How Social and Organizational Support Influence Online Teaching Experience in China? Exploring the Mediating Role of Technological Efficacy and Innovation Awareness - Weitong Liu; Ke Hu (SAGE Open)
The rapid shift to online education, accelerated by the COVID-19 pandemic, has fundamentally altered the landscape of teaching, and learning worldwide, making the exploration of factors influencing online teaching experiences increasingly vital. While existing research has examined the impact of instructional support on teaching efficacy and experience, a critical gap remains systematically exploring how personal, social, and organizational factors shape online teaching practices. This study aims to address this gap by investigating the relationships among social and organizational support, technological efficacy, innovation awareness, and online teaching effectiveness. Data collected from 3,154 university instructors across China were analyzed using structural equation modeling (SEM). The findings reveal that both technological efficacy and innovation awareness significantly mediate the relationship between social and organizational support and the online teaching experience. From the perspective of the standard total effect values, technological efficacy played a pivotal role in shaping the online teaching experience. These results contribute to the field by deepening our understanding of how support structures influence online teaching outcomes, providing empirical insights for strengthening support mechanisms that empower educators in technology-enhanced teaching environments.